2018
DOI: 10.4274/vhd.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hepatitis C Virus Genotypes in Aydın Province

Abstract: Objectives: In this study, we evaulated the distribution and alteration of hepatitis C virus (HCV) genotypes throughout years which has a clinical importance in the treatment and follow-up. Materials and Methods: Test results obtained from blood samples sent to the molecular microbiology laboratory at Aydın State Hospital for HCV genotype determination were analyzed retrospectively. A total of 182 samples collected between 2014 and 2018 were enrolled in the study. The determination of genotype and viral load o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
3
0
4
Order By: Relevance
“…The most common HCV genotype is genotype 1 worldwide, followed by genotype 3. Studies have reported genotype 1b to be the most frequently seen in Turkey (60%-100%) (18,19,20). However, in a 2015 study by Caliskan et al (21) of 313 HCV-RNA positive patients, genotype 3 was found at a rate of 46%.…”
Section: Discussionmentioning
confidence: 97%
“…The most common HCV genotype is genotype 1 worldwide, followed by genotype 3. Studies have reported genotype 1b to be the most frequently seen in Turkey (60%-100%) (18,19,20). However, in a 2015 study by Caliskan et al (21) of 313 HCV-RNA positive patients, genotype 3 was found at a rate of 46%.…”
Section: Discussionmentioning
confidence: 97%
“…Ülkemizdeki 2016 yılından itibaren son altı yıla ait güncel veriler incelendiğinde, Genotip 1b'nin %38.8-%85.8 arasında değişen oranlarla birlikte hala baskın genotip olduğu görülmektedir (Tablo 2). Yıllar içindeki dağılıma bakıldığında ise genotip 1b'nin oransal olarak yıllar içinde azaldığını belirten çalışmalar (1,9,11,14,26) olduğu gibi, anlamlı bir değişimin gözlemlenmediğini belirten yayınlar da mevcuttur (2,5) . Çalışmamızda 1b, %59.3 ile en sık saptanan genotip olmuş (Tablo 1) ve sadece 2018 yılında 2016 yılına göre bir yükseliş saptanmıştır, bunun dışında diğer yıllarda anlamlı bir değişiklik göstermemiştir (Tablo 2).…”
Section: Discussionunclassified
“…Ülkemizde yapılan son güncel çalışmalara göre Genotip 4 sıklığı %0-11 arasında değişmektedir. Bu çalışmalarda Genotip 4'ün yıllar içinde arttığı, özellikle savaş sonrası göç sebebiyle Orta Doğu kökenli kişilerin yoğun olduğu bölgelerde diğer bölgelere oranla daha sık saptandığı belirtilmiştir (3,8,18,26) . Bu bölgelerden biri olan İstanbul'da yapılan çalışmalarda farklı sonuçlar elde edilmiştir.…”
Section: Discussionunclassified
“…The European Research Journal 2022 total of 1-4% of patients develop hepatocellular carcinoma [5]. Although a meta-analysis study showed that the global incidence of HCV infection decreased, mathematical models show that deaths due to secondary liver disease in HCV infection will continue to increase [6].…”
Section: Early Onlinementioning
confidence: 99%